2002
DOI: 10.1097/00005176-200210000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of Preterm Formula With Long Chain Polyunsaturated Fatty Acids on Mineral Balance in Preterm Infants

Abstract: Adding a content of LCP blend similar to that of human milk to a preterm formula caused no disturbance in Ca, P, Mg, Zn, or Cu nutritional balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Consistent with these findings, Martinez et al (7) reported that supplementation of preterm formula with ARA and DHA caused no disturbances in mineral balance. Studies with rodents (14,44), piglets (45), and chicks (46,47), however, have reported effects of n-6 fatty acids (linoleic acid and ARA) and n-3 fatty acids (EPA and DHA) on bone formation.…”
mentioning
confidence: 63%
“…Consistent with these findings, Martinez et al (7) reported that supplementation of preterm formula with ARA and DHA caused no disturbances in mineral balance. Studies with rodents (14,44), piglets (45), and chicks (46,47), however, have reported effects of n-6 fatty acids (linoleic acid and ARA) and n-3 fatty acids (EPA and DHA) on bone formation.…”
mentioning
confidence: 63%
“…In piglets, calcium absorption was measured at 84%, whereas in rats, although the percentage of calcium absorbed was not stated, calcium absorption was increased by up to 45% (2). It is most likely that the differences between these two studies were due to the animal's developmental ages rather than the specific amounts of PUFAs because in human preterm infants dietary AA:DHA also did not affect mineral balance (4).…”
Section: Discussionmentioning
confidence: 95%
“…Today, most companies have marketed formula containing AA and DHA, yet the effect of formula with and without AA and DHA on bone mineralization and calcium balance remains unclear. In preterm infants, dietary AA as 0.5 g/100 g of fat and DHA as 0.3 g/100 g of fat in formula had no effect on mineral balance (calcium, phosphorus, magnesium, zinc) (4). Also in preterm infants, dietary AA (0.46 g/100 g of fat) and DHA (0.26 g/ 100 g until hospital discharge followed by 0.16 g/100 g of fat) in formula had no benefits to bone mass through to 1 y corrected age (5).…”
mentioning
confidence: 94%
“…A total of fourteen studies on zinc retention were identified [11,[17][18][19][21][22][23][24][25][26][27][28][29][30] with data on forty-five distinctly identifiable groups (Tables 1 and 2). All studies were identified in the primary PubMed search.…”
Section: Zincmentioning
confidence: 99%
“…Eleven studies measured copper balance [11,[17][18][19][23][24][25]27,30], all of which also reported data for zinc balance. Thirty-two distinct groups were identified (Table 3).…”
Section: Coppermentioning
confidence: 99%